1998
DOI: 10.1002/chin.199814008
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Phase Transition and Crystal Structures of LiSn2(PO4)3.

Abstract: structure structure (solids and liquids) D 2000 -008Phase Transition and Crystal Structures of LiSn 2 (PO 4 ) 3 .-Compound (IV) shows a reversible phase transition from rhombohedral (space group Rr3rc, Z = 6, 450 K) to triclinic (Pr1r, Z = 2, 250 K) monitored by powder X-ray and neutron diffraction, DSC and 31 P and 7 Li MAS NMR. The high temperature phase has a NASICON-type structure which is responsible for the relationship between conductivity and activation energy. The low temperature phase is a structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 0 publications
0
37
0
Order By: Relevance
“…Crystallographic structures have been reported for compounds based on tetravalent hafnium, titanium, germanium and tin and in every case a high temperature phase has been reported with rhombohedral symmetry that suggests the formation of phases isostructural with a-LiZr 2 (PO 4 ) 3 . [99][100][101][102] Whilst this is broadly correct there remain some differences in the crystallographic models used to describe these structures. For example a characterisation of a sample described as 'LiHf 2 (PO 4 ) 3 ' identified the presence of disordered lithium cations in the elongated octahedral site occupied in the a LiZr 2 (PO 4 ) 3 structure, but could not identify any additional lithium in the structure and concluded that the negative charge of the anionic framework was balanced by a small quantity of extra-framework hafnium.…”
Section: Doped Analogues Of Lizr 2 (Po 4 )mentioning
confidence: 99%
See 1 more Smart Citation
“…Crystallographic structures have been reported for compounds based on tetravalent hafnium, titanium, germanium and tin and in every case a high temperature phase has been reported with rhombohedral symmetry that suggests the formation of phases isostructural with a-LiZr 2 (PO 4 ) 3 . [99][100][101][102] Whilst this is broadly correct there remain some differences in the crystallographic models used to describe these structures. For example a characterisation of a sample described as 'LiHf 2 (PO 4 ) 3 ' identified the presence of disordered lithium cations in the elongated octahedral site occupied in the a LiZr 2 (PO 4 ) 3 structure, but could not identify any additional lithium in the structure and concluded that the negative charge of the anionic framework was balanced by a small quantity of extra-framework hafnium.…”
Section: Doped Analogues Of Lizr 2 (Po 4 )mentioning
confidence: 99%
“…[105] In addition to replacing Zr 4þ with elements in the same group it is possible to stabilise the rhombohedral structure using the d 10 cations Ge 4þ and Sn 4þ . LiSn 2 (PO 4 ) 3 contains lithium in a filled six-coordinate site [101] that makes it a direct analogue of LiTi 2 (PO 4 ) 3 . However, LiGe 2 (PO 4 ) 3 contains lithium in the octahedron, but displaced from the central position onto a partially occupied site [102] in a similar manner to that reported for a-LiZr 2 (PO 4 ) 3 .…”
Section: Doped Analogues Of Lizr 2 (Po 4 )mentioning
confidence: 99%
“…Its conductivity can be increased by partial substitution of Ti 4+ by trivalent cations; of which Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 [LATP] shows ionic conductivity as high as 10 À 3 Scm À 1 at room temperature [10]. A number of attempts have been reported in literature to increase the conductivity of LATP further, which include various synthesis and sintering techniques [11] and partial substitution of phosphorous in LATP by pentavalent cations like V 5+ , Nb 5+ and Ta 5+ .…”
Section: Introductionmentioning
confidence: 99%
“…NASICON (Na Super Ionic CONductor) type, A x B 2 (PO 4 ) 3 , materials have been extensively studied because of their high ionic conductivity at room temperature. In NASICON type material, the negatively charged 3D frame-work of general formula, B 2 (PO 4 ) 3 is made up of corner sharing BO 6 octahedra and PO 4 tetrahedra [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation